Cena życia. Mitologiczne fantazje i psychologia w powieści "Novendialia" ukraińskiej pisarki Maryny Sokolian = The price of life. Mythologic fantasies and psychology in the novel "Novendialia" by a Ukrainian writer Maryna Sokolian - Ajdačić, Dejan (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The novel entitled "Novendialia" (2008) by a Ukrainian authoress Maryna Sokolian (1979) with elements of a detective story and urban horror tells about fights between life energy kidnappers and its defenders employed by the Night Town Hall.
Keywords: literatura ukraińska; miejska fantasy; fantastyka; anima; libido; witalizm; wampir; religia; psychologia; Sokolian, Maryna (1979 -); Ukrainian literature; urban fantasy; fantasy; vitalism; vampire; religion; psychology